Pelestarian Tradisi Lisan Baroah Masyarakat Dayak Kanayatn di Dusun Ayo Gundaleng Kecamatan Sengah Temila Kabupaten Landak - Dodi Dores, Florianus; Andang Firmansyah; Astrini Eka Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the preservation of oral traditions Baroah Dayak Kanayatn. This study uses qualitative research with ethnographic approach. Data collection techniques used are observation, interview, and documentation techniques. Data analysis was conducted in three stages, namely data reduction, Data presentation, and Conclusion/verification. The results of this study indicate that the oral tradition of Baroah is still carried out by the Dayak Kanayatn community in Ayo Gundaleng Hamlet, Sengah District, Temila, Landak Regency. The efforts of the Dayak Kanayatn community in preserving the oral tradition of Baroah are routinely carried out every year. With routinely carried out every year, makaq small possibility of this tradition can be forgotten by future generations. Because they are directly involved and witness the stages of implementation. In addition, efforts to preserve the oral tradition of Baroah certainly can not be separated from the role of traditional leaders such as Temenggung, Pasirah, and Panyangahatn as well as the community to jointly preserve the tradition. Where their role to preserve the oral tradition of Baroah can be done by paying attention to culture or tradition, inviting, providing guidance, and direction. And understanding to the next generation to maintain the oral tradition of this Baroah in order to continue to run.